A Study on benefits of Utilizing RFID in Business Operations: Exploring the Impact of RFID Technology on Business Operations (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The research focuses on the various elements that drive technology adoption and thechallenges firms face while implementing new technologies in business operations. In addition,numerous RFID applications for industrial businesses are acknowledged, along with the benefits ofdoing so. The data demonstrate that RFID technology has a wide range of possible industrialapplications. Several factors influence technology adoption, but the perceived benefits of RFIDtechnology are frequently the most significant. Since RFID technology offers several benefits, effortsshould be made to establish implementation guidelines. All applications improve operational and supplychain management efficiency. According to the conclusions of the study, RFID technology has increasedthe productivity of industrial firms. This study seeks to comprehend how RFID technology usageimpacts businesses.